DETERMINANTS OF LOAN REPAYMENT OF THE SHRIMP HOUSEHOLDS: AN EMPIRICAL STUDY IN CA MAU PROVINCE, VIETNAM - Quang Vang DANG; Viet Thanh Truc TRAN; Hieu PHAM; Quoc Duy VUONG (Фінансово-кредитна діяльність: проблеми теорії та практики, 2022)
The aim of this paper was to analyze the determinant factors of the ability of shrimp farmers to repay loans on time and the decisive factors of the on-time loan repayment amount. Based on the primary data of 210 shrimp farming households in Ca Mau province, the study applied a two-step regression model of Heckman to test the proposed hypotheses. The research results showed that the number of dependent members, loan amount and number of farming crops negatively impact the ability to repay the loan in a timely manner, while total assets, shrimp farming experience and loan purpose positively influence the ability to repay the loan on time of shrimp households. In addition, the regression results also showed that number of loan maturity and size of shrimp farming land negatively affect the amount of on-time loan repayment, whereas the education level of the household head and total assets positively influence the on-time loan repayment amount. Based on the empirical findings, the authors proposed several recommendations for improving the loan repayment capacity of the households in the study area.